Monetary policy and inflation dynamics in ASEAN economies - Geraldine Dany-Knedlik; Juan Angel Garcia (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
This paper investigates the evolution of inflation dynamics in the five largest ASEAN countries between 1997 and 2017. To account for changes in the monetary policy frameworks since the Asian Financial Crisis (AFC), the analysis is based on country-specific Phillips Curves allowing for time-varying parameters. The paper finds evidence of a higher degree of forward-looking dynamics and a better anchoring of inflation expectations, consistent with the improvements in monetary policy frameworks in the region. In contrast, the quantitative impact of cyclical fluctuations and import prices has gradually diminished over time.
Keywords: C22; E31; E5; 330; Phillips curve; monetary policy; inflation expectations; ASEAN countries